Pengaruh Pembiayaan Mudharabah, Murabahah, Dan Ijarah Terhadap Laba Bersih: Studi kasus pada Bank BRI Syariah periode 2016-2020 - Nurma Indah Sari; Airin Nuraini (Institut Bisnis dan Informatika Kesatuan, 2022)
Islamic banks are financial institutions that are regulated according to sharia principles in providing credit or financing and other financial services, which have the function to expedite economic processes through business activities such as profit sharing (Mudharabah), buying and selling (Murabahah) and leasing (Ijarah) based on sharia values. This study aims to examine the effect of Mudharabah, Murabahah, and Ijarah Financing on Net Profit at BRI Syariah Bank for the 2016-2020 period. The population and sample in this study were the BRI Syariah Bank Monthly Financial Reports, January 2016 - December 2020, which amounted to 60 data. Samples were selected using the saturated sampling method. The analytical method used in this study is multiple linear regression with time series data processed using SPSS IBM.23 and Microsoft Excel 2010. The results of this study indicate that the independent variables Mudharabah, Murabahah, and Ijarah financing have a simultaneous effect on the dependent variable Net Profit. Mudharabah financing has no partial effect on Net Profit. Murabahah financing partially positive effect on Net Profit. Ijarah financing has a partial negative effect on Net Profit. Keywords: Mudharabah, Murabahah, Ijarah, and Net Profit